Ewolucja ustawodawstwa oświatowego w Anglii w XIX i XX wieku - Pyter, Magdalena (Czasopismo Prawno-Historyczne, 2018)
The issues raised in the article concern the development of education law in England from the enactment of the School Sites Act of 1841 to the enactment of the Education Act of 1944 which was the first comprehensive education act in England. Firstly, the article presents the reasons behind the rapid development of English education in the second half of the 19th century. Furthermore, the paper delineates the influence of the economy and of the industrialization on the systematic dissemination of education. Particular attention was paid to the spread of education to the masses at the primary level and to the education of the poorest people. The article presents the successively enacted legislative acts and legislative work conducted on them in various types of committees (royal committees, government committees). Also, the results of the work of these committees is discussed, i.e. the reports prepared by the said committees which later were the basis of legislative acts.